Factors Related To Postpartum Postpartum Visits In The Working Area Of The Kuala Lempuing Health Center, Bengkulu City Year 2024 - Porgasari, Julisti; Ningrum, Kartika Murya; Marlianto, Nuchemar (Jurnal Kesehatan Mitra Sekawan, 2026)
Based on World Health Organization (WHO) data, there are 140 million postpartum mothers that occur globally among women in 2019. The number of postpartum mothers according to the Ministry of Health of the Republic of Indonesia reached 5 million in 2019 from 34 provinces in Indonesia. The Bengkulu City Health Office in 2022 showed that there were 3,649 visits for postpartum mothers in Bengkulu city and 4,211 visits for postpartum visits in 2023. Based on data from the Kuala Lempuing Health Center in 2022, the number of pregnant women is 93 people and those who make postpartum visits are 29 people, in 2023 there are 144 pregnant women and 42 people who make visits. The purpose of this study is to find out the factors that affect the low number of postpartum visits in the working area of the Kuala Lempuing Health Center, Bengkulu City in 2024.The method used was a correlational descriptive research design with a cross sectional approach, with a simple random sampling technique of data collected by distributing questionnaires to 30 postpartum mothers. The results showed that there was a relationship between age and low postpartum visits with a value of p= 0.001, there was a relationship between education and low postpartum visits with a value of p= 0.000, and there was a relationship between parity and low postpartum visits with a value of p= 0.003 and there was a relationship between knowledge and low postpartum visits with a value of p= 0.000. This study can conclude that there is a relationship between age, education, parity, and knowledge with low postpartum visits in the working area of the Kuala Lempuing Health Center, Bengkulu City.